MAPPING THE VALUES OF THE ACCOUNTING PROFESSION FROM A NATIONAL DEFENSE PERSPECTIVE: A LITERATURE REVIEW - Rilah, Fitri Nur; Yuhertiana, Indrawati (Faculty of Economics and Business, 2025)
The accounting profession emphasizes the importance of ethical values as a basis for professional practice. This research aims to map the values of the accounting profession from the national defense perspective in order to build the character of accountants with integrity and national insight. The concept of national defense, deontological ethical theory, and labeling theory are theoretical foundations. The research method uses a systematic literature review with stages: classification of relevant literature in 2019-2024 using the Publish or Perish (PoP), VOSviewer, and Mendeley applications; found 20 articles with minimum criteria indexed by Sinta 4, Scopus, and others; presenting data in the form of narratives/images; final drawing of conclusions/findings. The results of the study show a mapping of 8 values of the accounting profession which are reflected in 5 values of national defense in the fishbone diagram and its application matrix: 1) Love for the Motherland (Integrity Values); 2) National and State Awareness (Professionalism Values and Public Trust Values); 3) Loyal to Pancasila (Divine Values and Justice Values); 4) Willing to Sacrifice (Loyalty Value); 5) Initial National Defense Capability (Accountability and Compliance Value); and 6) Social Responsibility (Sustainability Values). There are five critical points in the mapping process, as found in this research: integration, education, character, roles, and recommendations. This research implicated for the importance of integrating national defense values in the accounting curriculum, opportunities for empirical research on professional practice, and contributions to professional associations for sustainable social development.